Monitoring communications: aiming to identify periods of unusually increased communications between parties of interest. Issue 1 (2nd January 2016) - Sparks, Ross
Abstract: Monitoring to detect changes in the communication levels within a social network is a new area of research. There is little available on this topic in the current literature. This paper proposes that existing spatio-temporal surveillance technology could be used as a starting point for monitoring these changes. A number of challenges were encountered. The first involved the ordering of individuals into 'neighbours' so that the spatio-temporal surveillance technology and approaches could be applied. The second difficulty encountered was the computational effort involved in monitoring large numbers of individuals. In order to address this computational issue, cell communication level aggregation based on the order statistics of standardized cell communication count departures from expected was attempted. Simulations were used to compare two computationally feasible options.